Anamorelin for advanced non-small-cell lung cancer with cachexia: Systematic review and meta-analysis. (October 2017) - Nishie, Kenichi; Yamamoto, Shuhei; Nagata, Chie; Koizumi, Tomonobu; Hanaoka, Masayuki
Highlights: Total body weight and lean body muscle were significantly increased in the anamorelin group. Anamorelin significantly improved the quality of life. Anamorelin represents a promising treatment for cachexia in lung cancer patients. Abstract: Introduction: Cancer anorexia-cachexia syndrome (CACS) is characterized by involuntary weight loss. CACS is commonly observed in advanced non-small-cell lung cancer (NSCLC), and it leads to a poor quality of life (QOL). No effective standard treatment exists for this condition. However, anamorelin has reportedly caused improvement in patients with several cancers. Materials and methods: We conducted a quantitative meta-analysis to explore the efficacy of anamorelin for treating CACS in patients with NSCLC. We systematically searched CENTRAL, MEDLINE, EMBASE, CINAHL, and OvidSP. We pooled the data and calculated and compared total body weight (TBW), lean body mass (LBM), overall survival (OS), hand grip strength (HGS), QOL, and adverse events (AEs) between patients treated with anamorelin (anamorelin group) and those not (placebo group). Result: Six randomized controlled trials included 1641 patients with NSCLC. Both TBW and LBM were significantly increased in the anamorelin group compared to the placebo group (mean differences [MD] 1.78, 95%CI: 1.28–2.28, p < 0.00001; MD 1.10, 95%CI: 0.35–1.85, p = 0.004, respectively). The groups showed no difference in OS or HGS (hazard ratio 0.99, 95%CI: 0.85–1.14, p = 0.84; MD 0.52, 95% CI: −0.09–1.13, p = 0.09, respectively). Anamorelin significantly improved the QOL (standardized MD 0.19, 95%CI: 0.08–0.30, p = 0.0006). The frequency of any AEs and grade 3 or 4 AEs were not significantly different between groups (risk ratio[RR] 1.03, 95%CI: 0.95–1.10, p = 0.49; RR 0.86, 95%CI: 0.48–1.54, p = 0.62). Conclusion: This analysis demonstrated that anamorelin represents a promising treatment option for CACS in patients with advanced NSCLC.